Kecerdasan Emosional dan Kecerdasan Spiritual Menurut Dr. Ary Ginanjar Agustian: (Kajian Terhadap Buku Emotional Spiritual Quotient (ESQ) 165) - Muhammad Khoirul Afif; Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This study aims to examine the concept of spiritual intelligence and emotional intelligence according to Dr. Ary Ginanjar Agustian in the book Emotional Spiritual Quotient (ESQ) 165. This research is a library research with a qualitative descriptive approach. The data collection uses documentation techniques sourced from the book Emotional Spiritual Quotient (ESQ) 165 by Dr. Ary Ginanjar Agustian, also scientific literature and journals. The data analysis technique uses a qualitative descriptive analysis technique with data reduction steps, data presentation and drawing conclusions. The results of the research show that the concept of spiritual intelligence and emotional intelligence according to Dr. Ary Ginanjar Agustian in the book Emotional Spiritual Quotient (ESQ) 165. is material about leadership training and personality development in forming strong characters that combines the concepts of intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) in an integrated and transcendental manner in efforts to improve performance and productivity. In the ESQ way 165 book aimed at opening the gate to the heart dimension, it is found that basic values: honesty, justice, togetherness, creativity, true discipline, already exist in humans and are also basic human goals.